2018
DOI: 10.1016/j.celrep.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens Promote Misfolded Proinsulin Degradation to Protect Insulin Production and Delay Diabetes

Abstract: SUMMARY Conjugated estrogens (CE) delay the onset of type 2 diabetes (T2D) in postmenopausal women, but the mechanism is unclear. In T2D, the endoplasmic reticulum (ER) fails to promote proinsulin folding and, in failing to do so, promotes ER stress and βcell dysfunction. We show that CE prevent insulin-deficient diabetes in male and in female Akita mice using a model of misfolded proinsulin. CE stabilize the ER-associated protein degradation (ERAD) system and promote misfolded proinsulin proteasomal degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 57 publications
5
57
1
1
Order By: Relevance
“…The enhanced restoration of GLP-1R expression in dedifferentiated β cells by the GLP-1-oestrogen and insulin cotreatment renders them susceptible to targeted delivery of oestrogen. As has been proposed previously in the Akita mouse model 46 , we observed that stimulating the ERAD pathway by GLP-1-oestrogen beneficially influences β-cell physiology in rodent models of diabetes. In future studies, it might be of specific interest to test GLP-1-oestrogen with and without PEG-insulin co-therapy in genetically perturbed mouse models of ERAD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The enhanced restoration of GLP-1R expression in dedifferentiated β cells by the GLP-1-oestrogen and insulin cotreatment renders them susceptible to targeted delivery of oestrogen. As has been proposed previously in the Akita mouse model 46 , we observed that stimulating the ERAD pathway by GLP-1-oestrogen beneficially influences β-cell physiology in rodent models of diabetes. In future studies, it might be of specific interest to test GLP-1-oestrogen with and without PEG-insulin co-therapy in genetically perturbed mouse models of ERAD.…”
Section: Discussionsupporting
confidence: 82%
“…10b). Recently, it has been reported that oestrogen, via nuclear oestrogen receptor alpha signalling, stabilizes the ERAD proteins Sel1l and Hrd1in β cells, an effect associated with diabetes amelioration in Akita mice 46 . We observed increased costaining for insulin and Sel1l in GLP-1-oestrogen and PEG-insulin cotreated islets only 25 d after treatment initiation (Extended Data Fig.…”
Section: Ucn3mentioning
confidence: 99%
“…Recent in vitro studies using β cell lines suggested that Sel1L-Hrd1 ERAD may be involved in proinsulin degradation and maturation (37,38). Much to our surprise, in contrast to what these studies showed, we did not observe any significant changes in proinsulin maturation in Sel1L Ins1 islets, as demonstrated by the pulse-chase labeling of primary islets to follow nascent proinsulin biogenesis (Supplemental Figure 5D).…”
Section: Resultscontrasting
confidence: 93%
“…34 Overall, very little is known about the complex interplay between estrogen, ERs, and proteasome regulation, although estrogenic agents might have a relevant role in this process with consequences in health and disease. 50 Here we show for the first time that treatment with E2 and G1 increased USP19 levels in a time-dependent manner. The effect was detected already after 1 hour treatment, consistent with the rapid increase in PFKFB3 protein levels and the involvement of a membrane receptor.…”
mentioning
confidence: 53%
“…Previously, it has been shown that estrogenic agents increased the amount of E3 ligase and we cannot exclude an effect of estrogenic agents on E3 ligases in endothelial cells. 22,50 Interestingly, GPER silencing abolished the E2-mediated increase in USP19, further supporting the role of this receptor in the rapid posttranscriptional regulation of PFKFB3 levels. Upregulation of PFKFB3 levels linked to USP19 is required for the proangiogenic effect of GPER agonists, as shown by impaired estrogen-mediated HUVEC tubularization in USP19 knockdown cells ( Figure 7).…”
mentioning
confidence: 73%